Quality Assessment of 12 Lead ECG Signals based on Beat Detection Pattern - Muhammad Yazid (Department of Electrical Engineering ITS and FORTEI, 2017)
This paper proposed a new method for assessing signal quality from 12 lead ECG signal. The proposed method can be applied to incoming ECG data stream in one pass, does not involve computatively expensive filtering and does not require large memory space, which makes it especially useful for use in mobile device based ECG signal acquisition. The proposed method is verified on PhysioNet/Computing in Cardiology Chal- lenge 2011 12 lead ECG signals database, achieving a result of 89.98 percent accuracy when tested against the training dataset, and 87.4 percent accuracy when tested against the test data set. Keywords: ECG signal quality assessment